CHEMICAL CHARACTERISTICS OF CO-DRIED SILAGE FLOUR PATIN FLOUR (Pangasius hypophthalmus) WITH RICE IMMEDIATION AND DRY KNOWLEDGE - Era Yuliana; Bustari Hasan; Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThe catfish offal is taken from the catfish processing unit in one of the catfish processing centers in the village of Koto Masjid, Riau. The sample was taken to the laboratory and processed into silage, added 15% molasses by weight of the sample and fermented for 14 days (pH ± 4). Silage was mixed-dry with rice bran and dry tofu dregs and oven for 23 hours at a temperature (55oC) and evaluated for physical characteristics (color, aroma and texture), proximate composition (moisture content, protein content, fat content and ash cadar), NPN (Non protein nitrogen), amino acids, and pH. Rice bran silage flour contains lower levels of protein, water content, NPN and amino acids than dry tofu dregs silage flour, higher fat and ash than dry tofu dregs silage flour. Silage flour mixed with dry rice bran is darker brown , the aroma is less sharp, the texture is rough, the water content is 4.32%, the protein content is 30.06%, the fat content is 14.20%, the ash content is 19.44%, the NPN content is 20.88%, and the amino acid is 10.778%. While the SA silage flour is light brown, has a sharp acidic aroma, smooth texture, water content of 5.21%, protein content of 35.25%, fat content 13.14%, ash content 10.35%, 23.40% NPN content, amino acids 11,225%.Keywords: Silage flour, rice bran and dry tofu dregs